The Effectiveness of the Application of Snakes and Ladders Game in Mathematics Learning to Improve Student Learning Outcomes in Elementary Schools: A Systematic Literature Review - Siti Nur Fadila; Junaidi; Berta Apriza (Universitas Pendidikan Ganesha, 2025)
Mathematics learning at the elementary level faces challenges related to students’ difficulties in understanding abstract concepts and low learning motivation due to monotonous instructional methods. This condition highlights the need for innovative and engaging learning strategies. This study aims to systematically analyze the effectiveness of the snakes and ladders game in improving elementary students’ mathematics learning outcomes, motivation, and participation. This research employed a Systematic Literature Review (SLR) method to synthesize findings from previous studies related to the use of snakes and ladders games in mathematics learning. The research subjects consisted of ten scientific articles published between 2020 and 2024 that examined the implementation of snakes and ladders games in elementary school mathematics learning. Data were collected through documentation techniques by searching articles from the Google Scholar database using relevant keywords and applying inclusion and exclusion criteria. Data analysis was conducted through thematic synthesis by categorizing research findings based on learning outcomes, affective aspects, and social skills development. The results of the study indicate that the consistent use of snakes and ladders games has a positive impact on improving students’ mathematics learning outcomes, increasing motivation, enhancing active participation, and supporting social interaction during the learning process. These findings suggest that snakes and ladders games can serve as an effective, simple, and engaging learning medium for mathematics instruction at the elementary school level.